Maternal hypothyroidism and subsequent metabolic outcomes in children: a systematic review and meta-analysis - Lucy Zhao; Inthuja Selvaratnam; Jessie Cunningham; Kristian B. Filion; Sonia M. Grandi (BMC, 2024)
Abstract Introduction As the fetus relies on maternal thyroid hormones in early pregnancy, maternal hypothyroidism plays an important role in fetal development. However, the association between maternal hypothyroidism and metabolic disease in offspring is unclear. Objective To examine the association between maternal hypothyroidism in pregnancy and metabolic outcomes (obesity, hypertension, type 2 diabetes mellitus, and dyslipidemia) in children < 18 years. Methods We systematically searched 5 databases from inception to May 2023. Eligible studies included cohort, case-control, and randomized controlled trials involving children born to mothers with or without hypothyroidism in pregnancy. Data were pooled across studies using random-effects models for outcomes reported in at least three studies. Quality assessment was performed using the ROBINS-E tool for observational studies and the Cochrane Risk of Bias tool for trials. Results The search identified 3221 articles, of which 7 studies were included (1 trial, 6 observational). All studies were conducted outside of North America and ranged in size from 250 to > 1 million children. The follow-up time ranged from 6 to 20 years. Included studies support an increased risk of hypertension and glucose dysregulation in offspring exposed to maternal hypothyroidism (hypertension: OR 1.08, 95% CI 0.75, 1.57 and HR 1.81, 95% CI 1.21, 2.69; diabetes: RR 2.7, 95% CI 0.7, 10). In the pooled analysis, maternal hypothyroidism was not associated with obesity in offspring (OR 1.04, 95% CI 0.64, 1.70). Conclusion This study found inconsistent evidence on the association between maternal hypothyroidism in pregnancy and metabolic outcomes in offspring, though associations with hypertension and glucose dysregulation are possible.